Community Based Monitoring and Planning in Maharashtra - Abhay Shukla; Shelly Saha; Nitin Jadhav (My University, 2013)
The case study analyzes community based monitoring of health services, one of the core strategies of NRHM to promote decentralized village and district level health planning and management. It documents and analyzes the diverse experiences of community action vis. a. vis. accountability of health services through organizing Jan Sunwais (Public Hearing).
Documentation based on diverse experiences of community based monitoring and planning of health services, an effective strategy proposed by NRHM.
Keywords: Rural Population with a Specific Focus on Women, Children, Poor and Mrginalized Population